1994
DOI: 10.3109/00048679409075646
|View full text |Cite
|
Sign up to set email alerts
|

Career choice and experience of distress amongst interns: A survey of New South Wales internship 1987-1990

Abstract: Successive cohorts of interns assigned to a Sydney teaching hospital since 1987 were interviewed at the beginning and end of their intern year to document factors influencing career choice and psychological morbidity, with comparisons between the graduates of the three NSW medical faculties. Intellectual challenge and altruism were the two most reported motivating factors in choosing Medicine. Many interns expressed regret at their career choice. Apart from anger, self-reported psychological morbidity during i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The support of medical administration was rated reasonably highly in our study. The importance of administrative support for doctors is probably under‐recognized by the hospital community, despite the fact that provisions for job‐sharing, fairness of rosters and opportunities for interacting with administrators are perceived as important (Hume & Wilhelm 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The support of medical administration was rated reasonably highly in our study. The importance of administrative support for doctors is probably under‐recognized by the hospital community, despite the fact that provisions for job‐sharing, fairness of rosters and opportunities for interacting with administrators are perceived as important (Hume & Wilhelm 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There has been little research into the problems facing junior doctors in Australia. Data from the states of New South Wales and Queensland suggest that the interns report a lack of feedback about their performance, and many believe that their patients' health may be suboptimal as a result of their care (Hume & Wilhelm 1994; Wise et al 1995). Recognition of these problems has led to an educational commitment to junior doctors by several organizations.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in hours and provision of some administrative support (e.g. phlebotomists, Postgraduate Medical Council and structured intern support) have been provided since an earlier study 5 , yet there are significant areas of stress and a fall in perceived health as measured by this study. There are few studies in the literature regarding new graduates starting jobs 17−19 .…”
Section: Comparison Of Recent Health For 301 Total Responses From Intmentioning
confidence: 95%
“…Studies from the United Kingdom, USA and Scandinavia have recognized that junior doctors experience high levels of stress, anxiety and depression during their first year as doctors 1,3,4 . However, other than the paper by Hume and Wilhelm 5 , there is little information on stress in Australian interns during their first postgraduate year, and there are no studies that have documented changes in self‐reported health and stress over a year or followed intern stress over a series of years.…”
Section: Comparison Of Recent Health For 301 Total Responses From Intmentioning
confidence: 99%
“…This will enable students to identify the core neuroscientific basis when confronted with fundamental concepts. An increase in hands‐on clinical experience during undergraduate years, career guidance, assertiveness training and time management skills should be included in the curriculum 23 …”
Section: Domains Of Teachingmentioning
confidence: 99%